Effects Of Coupon, Maturity, Liquidity, And Bond Rating On The Yields Of Banking Bonds - Putri, Rizavia Mardhika; Siregar, Hermanto; Andati, Trias (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
Banks as bond issuers must be able to offer attractive bond yields to investors. The study aims to determine the effect of characteristics of bonds such as coupons, maturity, liquidity and rating of bonds to bond yields. In addition, in the study also forecasting the yield of banking bonds in the next year. The sample in this study is BUKU 3 Bank bonds that are actively traded in the Indonesian bond market, with a purposive random sampling technique, then a sample of 14 bonds is selected from 7 banks. The data analysis technique uses panel data regression with the fixed effect model. The results showing coupons and maturities have a significant positive effect, then the rating variable bonds have a negative effect on bond yields. While the variable liquidity has no effect on bond yields. Forecasting results of bond yields using a time series forecasting relationship model of 14 bonds in the sample there are 13 bonds showing a decreasing yield trend and only 1 bond showing an increasing yield trend.